Alamethicin self-assembling in lipid membranes: concentration dependence from pulsed EPR of spin labels. Issue 5 (17th January 2018) - Syryamina, Victoria N.; De Zotti, Marta; Toniolo, Claudio; Formaggio, Fernando; Dzuba, Sergei A.
Abstract : The antimicrobial action of the peptide antibiotic alamethicin (Alm) is commonly related to peptide self-assembling resulting in the formation of voltage-dependent channels in bacterial membranes, which induces ion permeation. Abstract : The antimicrobial action of the peptide antibiotic alamethicin (Alm) is commonly related to peptide self-assembling resulting in the formation of voltage-dependent channels in bacterial membranes, which induces ion permeation. To obtain a deeper insight into the mechanism of channel formation, it is useful to know the dependence of self-assembling on peptide concentration. With this aim, we studied Alm F50/5 spin-labeled analogs in a model 1-palmitoyl-2-oleoyl- sn-glycero -3-phosphocholine (POPC) membrane, for peptide-to-lipid (P/L) ratios varying between 1/1500 and 1/100. Pulsed electron–electron double resonance (PELDOR) spectroscopy reveals that even at the lowest concentration investigated, the Alm molecules assemble into dimers. Moreover, under these conditions, electron spin echo envelope modulation (ESEEM) spectroscopy of D2 O-hydrated membranes shows an abrupt change from the in-plane to the trans-membrane orientation of the peptide. Therefore, we hypothesize that dimer formation and peptide reorientation are concurrent processes and represent the initial step of peptide self-assembling. By increasing peptide concentration, higher oligomers are formed. A simple kinetic model of equilibrium among monomers, dimers, and pentamers allows for satisfactorily describing the experimental PELDOR data. The inter-label distances in the oligomers obtained from PELDOR experiments become better resolved with increasing P/L ratio, thus suggesting that the supramolecular organization of the higher-order oligomers becomes more defined.